Evaluation of Steel Clad Plate Weldability Using Ram Tensile Test Method - ZATORSKI, Z. (Engineering Transactions, 2014)
The weldability evaluation of steel clad plate is performed using the ram tensile test method. Numerical analysis of the considered problem is performed using the finite element method. The author introduces and verifies a critical ram tension strength R0 above the yield strength RIIe – as the criterion of the weldability evaluation of clad steel plate, where: RIIe =RIe < 0:707, RIIe, RIe – yield strengths of soft and hard materials.